Establishing the research priorities of paediatric emergency medicine clinicians in the UK and Ireland. Issue 11 (12th February 2015) - Hartshorn, Stuart; O'Sullivan, Ronan; Maconochie, Ian K; Bevan, Catherine; Cleugh, Francesca; Lyttle, Mark D
Abstract : Objective: Paediatric Emergency Research in the UK and Ireland (PERUKI) is a collaborative clinical studies group established in August 2012. It consists of a network of 43 centres from England, Ireland, Northern Ireland, Scotland and Wales, and aims to improve the emergency care of children through the performance of robust collaborative multicentre research within emergency departments. A study was conducted regarding the research priorities of PERUKI, to establish the research agenda for paediatric emergency medicine in the UK and Ireland. Methods: A two-stage modified Delphi survey was conducted of PERUKI members via an online survey platform. Stage 1 allowed each member to submit up to 12 individual questions that they identified as priorities for future research. In stage 2, the shortlisted questions were each rated on a seven-point Likert scale of relative importance. Participants: Members of PERUKI, including clinical specialists, academics, trainees and research nurses. Results: Stage 1 surveys were submitted by 46/91 PERUKI members (51%). A total of 249 research questions were generated and, following the removal of duplicate questions and shortlisting, 60 questions were carried forward for stage 2 ranking. Stage 2 survey responses were submitted by 58/95 members (61%). For the 60 research questions that were rated, the mean score of 'relative degree of importance' was 4.70 (range 3.36–5.62, SD 0.55). After ranking, the top 10 research priorities included questions on biomarkers for serious bacterial illness, major trauma, intravenous bronchodilators for asthma and decision rules for fever with petechiae, head injury and atraumatic limp. Conclusions: Research priorities of PERUKI members have been identified. By sharing these results with clinicians, academics and funding bodies, future research efforts can be focused to the areas of greatest need.